(untitled) (REMUNOM, 2025)
Currently, depression is the most common psychological disorder, identified as a mood disorder that modifies individuals’ attitudes and perceptions. In addition, anxiety disorder is also frequent in the population and is classified as a feeling of fear, vague and unpleasant, that arises as discomfort or tension. The Pilates Method operates through a combination of principles of mental control, body awareness, and physical strengthening. This study aimed to analyze the effects of Pilates on the postural and psychosocial rehabilitation of adolescents treated at a Child and Adolescent Psychosocial Care Center (CAPS). The research is characterized as action research, conducted with five female adolescents undergoing treatment for anxiety disorder and/or depression. A physiotherapeutic postural assessment form and the Rosenberg Self-Esteem Scale were used as instruments. The data were analyzed descriptively and organized into spreadsheets using Microsoft Excel. The results showed important postural alterations before the intervention, including forward head posture, shoulder protraction, lumbar hyperlordosis, protuberant abdomen, and asymmetries of the scapulae and pelvis. After the interventions, 40% of the sample showed significant improvement in these parameters, especially in cervical realignment, pelvic normalization, and reduction of hyperlordosis. Goniometry revealed relevant functional improvement in one of the adolescents, with increased symmetry and range of motion. In the psychosocial aspect, although the self-esteem classifications remained the same between evaluations, there was an increase in scores among 100% of the participants, indicating improvement in self-perception and emotional well-being. These findings support the literature that identifies Pilates as an effective resource for postural adjustments and the improvement of emotional symptoms. It is concluded that the Pilates Method has therapeutic potential in multiprofessional mental health care, contributing to the psychosocial and postural rehabilitation of adolescents. Despite limitations related to adherence and the short intervention period, the results highlight the relevance of continuing and expanding this practice in psychosocial care settings.